Penatalaksanaan Fisioterapi pada Kasus Osteoarthritis Genu Sinistra dengan Modalitas Mulligan Mobilization With Movement dan Kinesiotapping - Jumarna Jumarna; Wanti Hasmar; Indah Permata Sari (Prosiding Seminar Kesehatan Nasional, 2022)
Osteoarthritis genu is a degeneratif pain of knee articulation because there is abrasi of articulation born and shaping new born of interface articulation. Osteoarthritis genu causes by a few factor risk include age factor, gender, obesity, genetic, and activity making articulation knee. For knowing used fisioterapi placed of affair osteoatrhritis knee sinistra with method mulligan mobilization with movement and kinesiotapping can make storeyed articulation movement and minimized pain. After doing physiotherapy with method mulligan mobilization with movement and kinesiotapping as long 4x teraphy. Get result there is up joint range of motion and a decrease in pain. Mulligan mobilization with movement and kinesiotapping can increase joint range of motion and reduce pain.